Integrating Behavior and Technology-based Quality Management System to Improve Raw Milk Quality Collected by Bandung Dairy Cooperative - Meita Annisa Nurhutami; Dermawan Wibisono (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
Abstract. Milk quality is represented by Total Plate Count (TPC) value, the indicator of microbial contamination number in milk after production. The standard value is determined and set by the Codex and SNI 3141:1:2011 standards. The higher the TPC value, the lower the quality of the raw milk. This value determines the category of milk quality which impacts the payment scheme and the quantity of milk supplied to the Milk Processing Industry. As a consequence, farmers who collected lower quality milk received unfavorable financial outcomes.The aim of the research was to eliminate defects in milk quality by focusing on the quality control in the production system using Six Sigma approach. The Defects per Million Opportunity (DPMO) calculation was used to measure the quality of product in every one million opportunities. In this study, the DPMO showed 155,854 defects in every one million milk bulk collection held in 5 TPK. Two factors which decreased milk quality were the contamination in the milking process and in the milk collection process.To overcome the issue, technology and behavioral-based quality management systems are integrated to control the milk production and collection effectively and efficiently. Digital milk collection point is proposed to avoid contamination during milk collection through digitalization of data recording, milk test performed to individual samples, and access to test results. The digitalization can decrease the required time of milk collection and testing process. To raise the awareness of farmers towards quality and good farming practice, barn inspection is implemented using farming procedure infographics, Good Farming Practice training, and farmer certification.Keyword. quality management system; dairy industry; digital milk collection; technology; behavior